Prezydent Ukrainy a Krajowa Rada Ukrainy Radiofonii i Telewizji - Travinska, Svitlana (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2010)
This paper discusses the importance, organization, legal framework and history of an organ of state authority in Ukraine, namely the National Council for Television and Radio Broadcasting. The paper analyzes Ukrainian legal acts regulating the activity of organs in the realm of information. The purpose of the study is to explain the structure of the organs of executive power in the realm of the media and the process of their establishment and development. It also presents the powers of the President with respect to the National Council. The study aims to determine the status, position and function of the present government institution in the Ukrainian press system. Given this main aim, it is necessary to present the National Council as a legitimate institution regulated by a series of legitimizing provisions. It is of no lesser importance to determine and describe mutual relations between legal regulations and the activities of the National Board. The analysis of the Ukrainian normative acts allows one to answer questions about the essence and foundations of the National Council for Television and Radio Broadcasting’s activity and functions.